Acute heart failure : putting the puzzle of pathophysiology and evidence together in daily practice - Krüger, Wolfgang 1950- (Birkhaüser Verlag, 2009)
Acute heart failure is a potentially life threatening situation where correct, rapid therapy can have a life saving impact. In this rapidly changing area of medicine this text aims to bring the latest understanding of the pathophysiology together with a practical guide to diagnosis and management using a thoroughly evidence based approach. This will appeal to a wide audience of health care professionals who will treat patients with acute heart failure, including doctors, medical students, nurses, and other professionals in the Emergency Department, General Internal Medicine, Anaesthetics, Cardiology (Medicine and Surgery) and Critical Care settings. It may be used as an evidence based guide for the junior practitioner or as an aide-memoire for the more senior. Always keeping the underlying pathophysiology at the forefront of the discussion, the reader is encouraged to understand the aetiology of the acute situation and how to direct management in order to correct the abnormal physiology. Each chapter is heavily referenced allowing the reader to easily refer to the original experimental studies and pursue topics in more detail if required. This text is a valuable addition to any practitioner who treats patients with acute heart failure and wants a deeper understanding of the condition.